2022
DOI: 10.1093/ofid/ofac498
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium genavense Infections in Immunocompromised Patients Without HIV: Case Series of Solid Organ Transplant Patients and Literature Review

Abstract: Background Mycobacterium genavense infection is rare and can occur in non-HIV immunocompromised patients. Methods We describe two cases of M. genavense infection in patients with solid organ transplant (SOT), and we performed a literature review of non-HIV immunocompromised patients. Results 52 cases are reported. Predisposing factors were recipients of SOT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 79 publications
(102 reference statements)
0
5
0
6
Order By: Relevance
“…Indeed, the delay between the first symptoms of IRIS and the first treatment of IRIS is, on average, nine months, and between the first symptoms of IRIS and infliximab is, on average, 22 months in the case of our patients. Thus, unlike IRIS described by Manion and Baldolli [ 21 , 22 ] happened within weeks of infection diagnosis, the late-onset of IRIS presented by our patients and by the case of Laurent et al (17 months) has until now never been reported in scientific literature and should encourage clinicians to discuss this diagnosis in all patients with clinical worsening irrespective of the delay related to M. genavense initial diagnosis [ 23 ]. Therefore, late-onset IRIS has also been described in other opportunistic infections among HIV patients.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Indeed, the delay between the first symptoms of IRIS and the first treatment of IRIS is, on average, nine months, and between the first symptoms of IRIS and infliximab is, on average, 22 months in the case of our patients. Thus, unlike IRIS described by Manion and Baldolli [ 21 , 22 ] happened within weeks of infection diagnosis, the late-onset of IRIS presented by our patients and by the case of Laurent et al (17 months) has until now never been reported in scientific literature and should encourage clinicians to discuss this diagnosis in all patients with clinical worsening irrespective of the delay related to M. genavense initial diagnosis [ 23 ]. Therefore, late-onset IRIS has also been described in other opportunistic infections among HIV patients.…”
Section: Discussionmentioning
confidence: 43%
“…The use of anti-TNF-α in NTM IRIS is less described. Two case reports have been published concerning successful treatment with infliximab in steroid-dependent IRIS due to disseminated M. genavense disease, with a favorable clinical and radiological outcome for both patients [ 21 , 22 ]. To qualify, a case recently reported by Laurent et al described a late-onset (after seven years) fatal multi-refractory IRIS related to M. genavense in an HIV patient with ascites and portal thrombosis despite an increased dose of infliximab (10 mg/kg/month) and concomitant treatment with corticosteroids and colchicine [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…M. genavense has been detected more frequently in HIV patients [ 5 , 12 ]. Despite this fact, multiple reports have discussed M. genavense infection in non-HIV immunodeficiencies, namely sarcoidosis, solid organ recipients, and primary immunodeficiencies [ 14 17 ]. Diagnostic and treatment challenges are the most significant challenges in disease management.…”
Section: Discussionmentioning
confidence: 99%
“…Other NTM such as M. saskatchewanense and M. genavense are found in clinical samples from humans in North America and Europe, acting as opportunistic pathogens in immunocompromised patients ( 60 , 61 ). M. genavense has been reported in various wild and domestic animals, including birds, rabbits, cats, ferrets, snakes, and dogs ( 62 64 ). According to most authors, transmission to humans occurs through oral ingestion from contaminated water or close contact with infected animals.…”
Section: Discussionmentioning
confidence: 99%